Legal regulations of subordinated work rendered by free men in ancient Rome - Arévalo Vela, Javier (2019)
With the aim of dismissing the mistaken idea of some lawyers and judges that the right to work and employment was born in Ancient Rome, hereinbelow we shall explain the subordinated labor regulations that existed in Romulus’s homeland, affirming that the historical birth of the right to work must not be sought in Roman Law but in the protective laws that, for certain types of employees, arose as a result of the Industrial Revolution.